PENGARUH KEPEMIMPINAN, KOMPENSASI DAN IKLIM ORGANISASI TERHADAP MOTIVASI KERJA PEGAWAI DINAS SOSIAL DAN TENAGA KERJA KOTA PADANG PANJANG - Hartati Hartati; Yasri Hasim (Program Studi Magister Manajemen, 2014)
This study aims to find: 1) the influence of leadership on compensation, 2) the effect of leadership on organizational climate, 3) the influence of leadership on employee motivation, 4) the effect of compensation on organizational climate, 5) the effect of compensation on employee motivation, 6) the effect of organizational climate on employee motivation on Department of Social and Labor of Padang Panjang City. Type of research is ex post-facto, the study population was employee of the Department of Social and Labor of Padang Panjang City. The technique Sampling is a sampling population. Samples numbered are 42 people. The technique data analysis used is the Path Analysis. The results of the study showed: 1) Leadership significant effect on compensation of employees in the Department of Social and Labor of Padang Panjang City, 2) Leadership significant effect on organizational climate at the Department of Social and Labor of Padang Panjang City, 3) Compensation significantly influence the organizational climate at the Department of Social and Labor of Padang Panjang City 4) Leadership significant effect on employee motivation in the Department of Social and Labor of Padang Panjang City, 5) Compensation significant effect on employee motivation in the Department of Socia and Labor of Padang Panjang City and, 6) Organizational Climate significant effect on the motivation of employees working at the Department of Social and Labor of Padang Panjang City. Keywords: Leadership, Compensation, Organizational Climate and Employee Work Motivation.